185 Eccentric hamstring strength and sprinting performance changes during the off-season in Spanish footballers. (3rd March 2020) - Vicens-Bordas, Jordi; Esteve, Ernest; Fort-Vanmeerhaeghe, Azahara; Casals, Martí; Bandholm, Thomas; Ishoi, Lasse; Opar, David; Shield, Anthony; Thorborg, Kristian
Abstract : Background: Low eccentric hamstring strength and sprinting performance are associated with hamstring injury (HI) in football; however, the off-season effects on both qualities are unknown. Objective: The aim of the study was to investigate eccentric hamstring strength and sprinting performance changes during the off-season period in football players. Design: Prospective cohort study. Setting: Semi-professional (3rd-4th tier) and amateur (5th-8th tier) Spanish footballers. Patients (or Participants): Male footballers (n=107) were contacted to participate. Seventy-four footballers (25±4 years, 178.0±6.6 cm, 74.9±8.1 kg) were included in final analyses. Interventions (or assessment of risk factors): Eccentric hamstring strength (Nordbord) and sprint performance (30m sprint and V-Cut test) were assessed at the beginning (May-June 2017) and end of the off-season (July-August 2017). Previous HI, age and off-season length were considered the independent variables. Main outcome measurements: Eccentric hamstring strength (N; N·kg -1 ), 30m sprint (5–10m splits (s)) and change-of-direction performance (s). All outcomes were proposed before any data collection. Data was analysed using paired t-tests and linear mixed models. Results: No changes in eccentric hamstring strength were found at follow-up. Large (2%, d=0.96; p<0.001) and small (1%, d=0.46; p<0.001) decrements in performance were found for 30m sprint and 10m split time at follow-up, respectively. Previous HI, age or off-season length had no effect on any of the outcomes. Conclusions: Footballers showed no reduction in eccentric hamstring strength but impaired sprint performance after the off-season period, independent of age, previous HI and length of off-season. This may suggest the risk of sustaining a HI during the pre-season is lowered, as a result of decreased maximal sprinting capacity. This implicates that introducing eccentric hamstring strengthening during pre/early season seems relevant as this may both increase sprinting performance and mitigate the risk of HI during the in-season.